Strategic analysis of limitations in high-performance machining systems - Alsigar Masar; Alhafadhi Mahmood (Results in Engineering)
Predicting machining precision in CNC machining of metal pipes presents considerable difficulty in the mechanical manufacturing industry. This is attributable to the absence of standardized instrumentation in most CAD/CAM systems to guarantee dimensional accuracy and surface quality. This study presents a novel scientific methodology employing the digital twin concept to develop a virtual simulation model to predict and improve the machining precision of cylindrical metal surfaces. The model combines mathematical and experimental methods to evaluate differences in cutting depth and geometric deviations during the final manufacturing phase, considering critical aspects such as cutting speed, feed rate, and material properties. The model facilitates accurate surface change prediction by simulating metal's mechanical responses under real manufacturing conditions. Experiments have shown that integrating the digital twins model into the design and operational planning stages significantly increases prediction accuracy, reduces material waste by up to 15 %, and improves the final quality of the metal pipe surface. The results illustrate the model's practical importance when improving CNC machining results.